Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1007/s10595-005-0040-5
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining pore shape in polycarbonate track membranes

Abstract: The formation of pores in polycarbonate films irradiated by accelerated ions upon their treatment with alkali solution containing a surfactant was studied. It was found that the pore shape is determined by both the structure of the initial film and the peculiarities of interaction of a surfactant with a polymer surface and its transfer to a track. Because of the inhomogeneity of the initial material, the "track" pore cross section varies along the pore length. The presence of a surfactant leads to an additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…For example, 60 nm diameter (Bi 1−x Sb x ) 2 Te 3 wires were grown in commercially available polycarbonate membranes (thickness 6 μm), 37 the wires displaying the so-called cigar-like shape of the hosting pores. 38,39 Additional works by Koukharenko et al 40 In this work, we explore the use of polymeric membranes for growth of Bi 2 Te 3 nanowires in further detail. We demonstrate that, by simultaneous tuning of all fabrication parameters, electrodeposition in polymeric membranes can be optimized to synthesize nanowires with sets of geometrical and crystallographic characteristics particulary interesting for both basic investigations of low-dimensional Bi 2 Te 3 nanomaterials (diameters below 20 nm, 3,4,6−8 controlled morphology, 8 and crystallographic structure 6 ), as well as for thermoelectric model systems and devices 42,43 (long wires to achieve and maintain a large enough temperature gradient, and possible integration to devices).…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, 60 nm diameter (Bi 1−x Sb x ) 2 Te 3 wires were grown in commercially available polycarbonate membranes (thickness 6 μm), 37 the wires displaying the so-called cigar-like shape of the hosting pores. 38,39 Additional works by Koukharenko et al 40 In this work, we explore the use of polymeric membranes for growth of Bi 2 Te 3 nanowires in further detail. We demonstrate that, by simultaneous tuning of all fabrication parameters, electrodeposition in polymeric membranes can be optimized to synthesize nanowires with sets of geometrical and crystallographic characteristics particulary interesting for both basic investigations of low-dimensional Bi 2 Te 3 nanomaterials (diameters below 20 nm, 3,4,6−8 controlled morphology, 8 and crystallographic structure 6 ), as well as for thermoelectric model systems and devices 42,43 (long wires to achieve and maintain a large enough temperature gradient, and possible integration to devices).…”
Section: ■ Introductionmentioning
confidence: 97%
“…Moreover, AAO membranes have been by far the most commonly used templates for the electrochemical deposition of Bi 2 Te 3 nanowires, and only very few experimental investigations have employed polymeric membranes. For example, 60 nm diameter (Bi 1– x Sb x ) 2 Te 3 wires were grown in commercially available polycarbonate membranes (thickness 6 μm), the wires displaying the so-called cigar-like shape of the hosting pores. , Additional works by Koukharenko et al and Frantz et al reported the growth of 80 nm diameter Bi 2 Te 3 nanowires in 20 μm thick polyimide (Kapton HN) and 60 nm diameter wires in 30 μm thick polycarbonate membranes (Makrofol N), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Shape of the pores in commercially available membranes is reported to be toothpick- or cigar-like [ 23 , 25 ]. The origin of such shapes is ascribed to the presence of surfactants in the etching solution [ 26 ]. The wires prepared in the commercial membranes are reported to be up to a factor 2.5 wider in the central part than at the ends [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the type of membrane material and the pore diameter, the manufacturing technique can be either chemical etching [56], ion-track etching [57], ion beam sculpting [58], helium ion beam [59], controlled dielectric breakdown [60], laser ablation [61], controlled optical etching [62], or electron beam carving [63]. The membranes can be made of polymers, such as polyethylene terephthalate (PET) [64] or polycarbonate [65], but they are most often made from inorganic materials such as silicon nitride (Si 3 N 4 ) [66], silicon oxide (SiO 2 ) [63], alumina (Al 2 O 3 ) [67], or hafnium oxide (HfO 2 ) [68]. Despite the very robust detection obtained with nanopores fabricated in these materials, their key problem was the high thickness of the membrane which can limit the resolution of sensing [69].…”
Section: Solid-state Poresmentioning
confidence: 99%